Pelatihan Pemanfaatan Gemini AI dan Quizizz dalam Penyusunan Perangkat dan Evaluasi Pembelajaran: Panduan Praktis untuk Guru di Gugus 2 Citalem - Ai Nurhayati; Asep Maulana Nurparid; Tias Siti Nurafifah; Rizka Nurhayati; M Gelar Faisal (LPMP Imperium, 2025)
This training is motivated by the problem of teachers who face obstacles in preparing learning tools and evaluations due to limited time due to busy schedules and not long work experience, which makes the preparation of learning administration less than optimal. Therefore, it needs to be improved through training on the use of Gemini AI and Quizz. This training aims to utilize technology effectively to improve the quality of learning in the classroom. SD Negeri Pasirbanteng became the location for this training and was attended by 45 teachers and held on September 07, 2024. The method used in this training is Service Learning (SL). The series of activities carried out are, identification of problems or needs, integration of academic learning, providing services, collaboration with community partners, reflection and evaluation Gemini AI and Quizizz training was carried out smoothly, providing in-depth understanding to teachers about the utilization of these two tools. The training resulted in participants' in-depth understanding and practical skills in utilizing AI technology and digital platforms for learning needs. Based on the activity evaluation, this training not only adds new insights, but also inspires teachers to improve the effectiveness and quality of learning in their classrooms. Thus, this training contributes to the application of innovative technologies in education.